Better coaching the Paralympics swimmers with the computed use of stroke rate-velocity relationship - Seyfried, D. (The Engineering of sport 7, Volume 2, 2008)
Modelling Paralympics swimmers for boosting individual performance. Abstract: A good number of mathematical relations found between the obtained speeds on dean swimming but equally on non-swim areas (starts, turns, underwater part) can be a source of potential help to the individual Paralympics swimmers if they can be computed. Looking to take the spontaneous frequency of swimming to take advantage of it in an applied way of better learning (for the swimmer) and better coaching has been a method we developed frorn 1993 in the national sport institute of Paris (INSEP) since it appeared to be the most effective in terms of swim economy. The stroke rate/velocity relationship is very interesting since its mastering has a lot of consequences on energy cost, delay of fatigue and better learning of the best stroke at any moment in training sessions or competitions. The stroke rate/velocity test is incremental and carried though the observation of 15 meters of clean swimming where 3 full cycles are measured considering the time and the spontaneous stroke rate of the swimmer, during 8 progressive steps. These starting points guided the development of several types of Software beneficial to swimming training including NATAVIT (1995-2000) and AQUACYCLE (since 2000) but equally a concept of measurement automated in training (CHRONOCYCLE) particularly useful for French Paralympics swimming team.